WiFi radio resource management - Valente, Pedro Brigas (2018)
Passive optical networks have been subject of research in recent years, standing out from the other distribution networks not only by the speed and distribution of multiple services, including video, data and voice, but also by the absence of active equipment between the central and terminal devices, not requiring the use of electricity. Also the progress made in mobile and "smart" equipment led to the increase of its popularity and personal use. The increase of mobile devices, as well as their features, were boosted by the evolution of WiFi technologies, mostly fueled by passive optical networks, favoring the connection of several devices through radio waves. There has been several improvements in wireless communications, especially in WiFi technology, in order to keep up with the speed increase in optical distribution networks. However the limitations in the frequency spectrum and the vast implementation of the technology itself became an obstacle to the development of WiFi networks. The main goal of this dissertation is the development of processes dedicated to the frequency spectrum management in WiFi networks within environments congestedbymultipleradiosignaltransmitters. Thisworkisdevelopedaround a gateway under development by Altice Labs combining optical network terminal and access point features, and presents a solution to the equipment transmission power management and the frequency channel selection.